Trends in antimicrobial utilization in a university hospital, 1990-1996 - Castro, Mauro Silveira de; Pilger, Diogo; Ferreira, Maria Beatriz Cardoso; Kopittke, Luciane (Revista de Saúde Pública, 2002)
OBJECTIVE: There is a worldwide concern about rational drug use, more specifically related to antimicrobial utilization. In developing countries, few resources are intended for monitoring on rational drug use. Moreover, there are limited data on the use of antimicrobial agents in hospitals. A study was carried out to describe patterns of use of antimicrobial agents over a 7-year period (1990 to 1996). METHODS: The study was conducted in a 690-bed tertiary care university hospital in Porto Alegre, Brazil. Hospital records were reviewed to identify inpatient antibiotics use. Results were expressed in defined daily dose per 100-beds/day. Cluster analysis was performed to determine the trends in use of individual agents. RESULTS: Antimicrobials use increased year after year, from 83.8 DDD per 100 beds-day in 1990 to 124.58 DDD per 100 beds-day in 1996. Penicillins were the drug group mostly used (39.6%), followed by cephalosporins (15.0%), aminoglycosides (14.4%), sulfonamides (12.8%), glycopeptides (3.6%), and lincosamides (3.1%). These groups were responsible for around 90% of all agents used. The use of antimicrobial agents was divided into thirteen groups based on cluster analysis. CONCLUSIONS: Antimicrobial use increased dramatically in the study period, and this increase was significantly higher when compared to other studies. When newer alternative agents became available in the hospital, the use of already existing drugs decreased and in some cases remained relatively stable. After implementing specific interventions, such as an effort for the correct use of cefoxitin, the expected changes in use were observed.